ANALISIS PENGARUH KUALITAS PRODUK, LOKASI, KEMAMPUAN INOVASI TERHADAP MINAT BELI ULANG BATIK TULIS TANJUNG BUMI - Juhoiriyah, Putri; Tarman, Manah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to analyze the influence of product quality, location, innovation ability and interest in repurchasing Tanjung Bumi handwritten batik. This type of research is quantitative research. The population in this research is all consumers who shop in the Tanjung Bumi batik industry, the number of which is unknown, meanwhile the sample used by researchers in conducting the research was 50 respondents. The data collection techniques that researchers used were in the form of questionnaires and observations. And the analysis techniques used are validity tests, reliability tests, normality tests, multiple linear regression tests (t test, f test). Based on the results of the research that has been carried out, it is known that product quality, location, innovation ability influence the interest in repurchasing Tanjung Bumi hand-written batik. This is proven by using the F test, where the average result of the decision to repurchase written batik is F_Count of 65.464 > F_Table of 2.81, so it can be concluded that H0 is rejected and Ha is accepted, meaning that the product quality variables (X1) location (X2), and innovation ability (X3) simultaneously influence the increase in repurchase interest (Y).